The performance of trait-based indices in an estuarine environment. (February 2016) - van der Linden, P.; Marchini, A.; Dolbeth, M.; Patrício, J.; Veríssimo, H.; Marques, J.C.
Highlights: Species traits responded to hydrological disturbance in an estuarine environment. The new SR-FRED index allowed combining the taxonomic and functional structure. CWM and SR-FRED provided the best overall picture regarding disturbance. Trait-based indices should be used with caution in estuarine ecosystems. Abstract: The performance of several indices of benthic functioning, based on the traits of estuarine macro-invertebrates, was tested in the lower Mondego estuary (Portugal), whose two arms exhibit different disturbance levels related to hydromorphology. The results showed that some indices responded clearly to this type of disturbance and others not so well. We argue that the community-weighted mean trait values (CWM) in combination with the newly developed SR-FRED index provided the best overall picture of how the benthic communities might have been affected by hydromorphological disturbance. This study also showed that certain indices should be used with caution when dealing with communities with few and dominant species, such as in estuarine environments.